Physical and chemical quality of riparian water bodies in the coastal zone of the Ballena Bay and Cortés Port Costa Rica (UNED Research Journal, 2019)
Introduction: various physical and biological factors affect coastal aquatic systems. Objective: to determine the physico-chemical conditions of four surface water bodies in Costa Rica. Methods: at each monitoring station the in situ value of the physical-chemical variables of the water was determined with a Thermo Scientific multi-parameter portable meter. Turbidity (Secchi), type of environment and current were categorized as "dummy" variables. Results: I took a total of 22 samples. Dissolved oxygen ranged b etween 8,73mg/L in Ballena Creek and 12,88mg/L in Coronado River; oxygen saturation from 137,2% in Tortuga River to 164,2% in Coronado River. Water temperature ranged from 25,20° C in Ballena Stream and 34,10°C in the Morete River; salinity ranged from 0.10ppt in the four sampling sites to 0.20ppt in the Morete and Coronado rivers. Total dissolved solids ranged from 64mg/L in Tortuga River to 173mg/L in Coronado River. The pH from 6,42 in Ballena Creek to 7,67 in the Coronado River. Conclusion: There were no significant differences among these rivers and streams: they all have a similar water quality.